Arts Education in Pesantren (Islamic Boarding School) : an Aesthetic Expression of Students’ Drawing in MTs Al Asror Semarang - Ma'sum, Aziz; Triyanto, Triyanto; Syarif, Muh. Ibnan (Universitas Negeri Semarang, 2018)
Pesantren Environment is an environment that has different characteristic from other environments. The research purpose is to observe the problem of aesthetic expression of Pesantren students’ drawing, the environment that influences them. Qualitative method was used with descriptive qualitative approach. Data collection techniques were observation, interview, and document study. data validity techniques used source triangulation, technique triangulation, and member checking. Data analysis procedure used data reduction, data presentation, and conclusion drawing. The research results show; first, aesthetic expression of students’ painting shows the visual uniqueness in the lines, looks, shapes, textures, colors, and aesthetic principles. Second, environment that influences, natural-physical environment, social environment, Pesantren cultural environment that is manifested in a form of any symbol that relates to Pesantren.